2009
DOI: 10.1007/s11469-009-9254-9
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Validation of a New Clinical Tool for Identifying Problem Video Game Playing

Abstract: Research has estimated that between 6 to 13% of individuals who play video games do so excessively. However, the methods and definitions used to identify "problem" video game players often vary considerably. This research presents preliminary validation data for a new measure of problematic video game play called the Problem Video Game Playing Test (PVGT). Two studies were conducted: an online survey of 373 university student video game players, and a paper-and-pencil survey of 416 video game players from vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 38 publications
5
56
1
1
Order By: Relevance
“…In terms of methodology, two case studies of male online gamers were included , large samples of adult MMORPG players (Charlton & Danforth, 2007), elementary school video gamers (Skoric, et al, 2009), student and non-student video game players (King, Delfabbro, & Zajac, 2009), teenagers (Salguero & Moran, 2002), elementary and high school students , and secondary school adolescents (van Rooij, et al, 2010).…”
Section: Classification/assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of methodology, two case studies of male online gamers were included , large samples of adult MMORPG players (Charlton & Danforth, 2007), elementary school video gamers (Skoric, et al, 2009), student and non-student video game players (King, Delfabbro, & Zajac, 2009), teenagers (Salguero & Moran, 2002), elementary and high school students , and secondary school adolescents (van Rooij, et al, 2010).…”
Section: Classification/assessmentmentioning
confidence: 99%
“…In each of the studies, different terminologies were applied for similar phenomena, ranging from compulsive Internet use (van Rooij, et al, 2010), problem video game playing (King, et al, 2009;Salguero & Moran, 2002) and problematic online game use to video game addiction (Skoric, et al, 2009) and online gaming addiction (Charlton & Danforth, 2007;. Similarly, a variety of measurement instruments was used in order to assess the specified problematic/addictive behaviors, namely the Compulsive Internet Use Scale (Meerkerk, Van Den Eijnden, Vermulst, & Garretsen, 2009), the Problematic Video Game Playing Test (adapted from Young, 1998), the Problem Video Game Playing Scale (Salguero & Moran, 2002), the Problematic Online Game Use Scale , an assessment of addiction tendencies (based on American Psychiatric Association, 2000), the Addiction-Engagement Questionnaire (modified from Charlton, 2002), and the Game Addiction Scale (based on Lemmens, Valkenburg, & Peter, 2009).…”
Section: Classification/assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians and researchers in allied mental health disciplines have proposed that, under certain conditions, video-gaming may become psychologically, socially, and/or physically detrimental to the user (e.g., Kuss & Griffiths, 2012a;Salguero & Moran, 2002). The question of whether a pattern of problematic video-gaming behaviors over a sustained period of time may constitute a psychological disorder is the topic of ongoing debate (Blaszczynski, 2006;King, Delfabbro, & Zajac, 2011;Wood, 2008). On May 1, 2012, the DSM-V Task Force and Work Groups proposed that Internet Use Disorder, which primarily refers to maladaptive video-gaming (or "Internet Gaming") behavior, should be included in Section III of the DSM-V as the subject of further empirical inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although video game addiction is not a formal diagnosis, studies have found that it is characterized by the same features as other behavioral addictions, including salience, tolerance, withdrawal, relapse, mood modification, and conflict. [12][13][14] Additionally, the problematic video game use construct can be reliably assessed, 15,16 has good construct validity, 17 and is associated with negative functional outcomes. 18 The primary diagnostic features of ASD include impairment in social and communication skills and engagement in restricted/repetitive behaviors.…”
mentioning
confidence: 99%